The Effect of Structured Literacy on Reading Skills of Fifth-Grade Students - Solehun, Solehun; Hartati, Tatat; Damayanti, Vismaia S (Journal of Innovation and Research in Primary Education, 2025)
Literacy is a foundational competency that significantly influences students’ academic and lifelong success. This study investigates the effect of structured literacy instruction on the reading abilities of Grade V students at SD Lab School UNIMUDA, Sorong Regency. Using a one-group pretest-posttest design, this quantitative study involved eight students and applied a literacy intervention integrated into Bahasa Indonesia instruction over the course of four sessions. Data were collected through pretests and posttests and analyzed using the Shapiro-Wilk normality test, paired sample t-test, and normalized gain (N-Gain) analysis. The findings indicate that the data were normally distributed, permitting the use of parametric analysis. The paired sample t-test showed a statistically significant improvement in students’ reading performance (p = 0.000), while the N-Gain score averaged 57.15%, placing the intervention in the moderately effective category. These results demonstrate that consistent and visually engaging literacy instruction, supported by structured routines and relevant reading materials, can enhance student engagement and reading comprehension. The study contributes to the existing literature by providing evidence from a remote and underrepresented educational setting, highlighting the effectiveness of school-based literacy initiatives. It calls for broader implementation of such interventions and suggests further research into sustainable and community-supported literacy models. The findings offer practical insights for educators, policymakers, and literacy advocates working to improve primary education outcomes.